Dolomite relief in the Žibrše hills - Komac, Blaž (Acta geographica Slovenica, 2003)
The paper describes the principal characteristics of dolomite relief with dells in the Žibrše hills northeast of Logatec. Considered geomorphologically, the studies of the geological structure and chemistry studies indicate that the dells were formed by periglacial processes during the cold periods of the Pleistocene, and due to the carbonate nature of the rock, by karst processes as well.
Keywords: fizična geografija; physical geography; geomorfologija; geomorphology; relief; topography; dolomit; Žibrše; Inner Carniola; Notranjska; Slovenia; Slovenija